Colour maps for fisheries acoustic echograms. (22nd December 2019) - Blackwell, Robert E; Harvey, Richard; Queste, Bastien Y; Fielding, Sophie
Abstract: Echograms are used to visualize fisheries acoustic data, but choice of colour map has a significant effect on appearance. Quantitative echograms should use colour maps, which are colourful (have a perceived variety and intensity of colours), sequential (have monotonic lightness), and perceptually uniform (have consistency of perceived colour contrast over their range). We measure whether colour maps are colourful (M ^ ( 3 ) > 0 ), sequential (r s = ± 1 ), and perceptually uniform ( ρ  = 1) using an approximately perceptually uniform colour space (CIELAB). Whilst all the fisheries acoustic colour maps tested are colourful, none is sequential or perceptually uniform. The widely used EK500 colour map is extremely colourful (M ^ ( 3 ) = 186 ), not sequential (r s = 0.06 ), and has highly uneven perceptual contrast over its range (ρ = 0.26 ). Of the fisheries acoustic colour maps tested, the Large Scale Survey System default colour map is least colourful (M ^ ( 3 ) = 79 ), but comes closest to being sequential (r s = − 0.94 ), and perceptually uniform (ρ = 0.95 ). Modern colour maps have been specifically designed for colour contrast consistency, accessibility for viewers with red-green colour-blindness, and legibility when printed in monochrome, and may be better suited to the presentation and interpretation of quantitative fisheries acoustic echograms.